Subjektivität und Intersubjektivität: zur Grundlage psychiatrischer und psychotherapeutischer Diagnostik - Fuchs, Thomas (Kontext, 2015)
Subjectivity and intersubjectivity in psychiatric diagnosis. The establishment of criteriological diagnostic systems since the 1980s has increased the reliability of psychiatric diagnosis. On the other hand, the limits of this approach for clinicians and researchers are becoming increasingly apparent, in particular, with regard to the missing assessment of subjective experience. To correct this unfavourable development, three major approaches to the assessment of mental illness should be equally taken into account: 1.) The positivistic, objectifying or 3rd person approach as endorsed by DSM-IV and ICD-10, 2.) the phenomenological, subject-oriented or 1st person approach,3.) the hermeneutic, intersubjective or 2nd person approach. These three approaches will be compared regarding their respective values for psychopathological description, diagnosis, research and therapeutic purposes.